AB0437 Predictivity of serum biomarkers for disease activity in a prospectively followed-up takayasu arteritis cohort: is serum amyloid a protein better than conventional acute phase markers?. (23rd January 2014) - Omma, A.; Erer, B.; Alpay, N.; Gurel Polat, N.; Gul, A.; Inanc, M.; Kamali, S.
Abstract : Background: Takayasu arteritis (TA) is a chronic vasculitis with an indolent course. Reliable diagnostic and activity markers have not yet been demonstrated. Objectives: We aimed to evaluate the predictivity of conventional acute phase proteins (ESR, CRP) and other non-conventional inflammation and endothelial activity markers such as serum amilod A (SAA) protein, interleukin-6 (IL-6) and von Willebrand factor (vWF) in a TA cohort, prospectively followed-up. Methods: Fourty-eight TA patients diagnosed according to ACR 1990 criteria and followed-up ≥ 6 months, 37 patients with granulomatosis with poliangiitis (GPA) diagnosed according to ACR 1990 criteria and 28 healthy controls (HC) were included into the study. Demographic and clinical features of TA, GPA and HCs were recorded into a predefined protocol. ESR, CRP, SAA, IL-6 and vWF levels were analysed initially in all groups and at 3 rd, 6 th, 12 th months visits in TA and GPA groups. Westergreen method for ESR, nephelometric assay for CRP, SAA and ELISA method for IL-6 and vWF were used. Disease activity was evaluated by Kerr criteria for TA and BVAS2003 for GPA. TA and GPA cohorts were stratified to the subgroups according to the activity. Comparisons were performed by Mann Whitney U test in subgroups. ROC curve analysis was used to identify the sensitivity and specificity of laboratory parameters for predicting activity. Results: Mean age and disease duration were found as 40±13 yrs, 121±115 mo for TA, 47±13 yrs, 65±42 mo for GPA and mean age was 38±9 for HCs. Females were significantly high in TA cohort (%) when compared to GPA (%) (p<0, 001). The percentage of active disease was 40%, 31%, 35%, 29% for TA and 32%, 19%, 11%, 13% for GPA at initial 3 rd, 6 th and 12 th months, respectively. ESR, CRP and SAA levels were significantly high in active TA at the initial, 3 rd and 6 th months visits (41±20 vs 21±12, p=<0.001 for ESR, 20±20 vs 6±10 p=<0.001 for CRP, 23±23 vs 12±29, p=0.001 for SAA at initial visit, 41±19 vs 24±17, p=0.002 for ESR, 26±28 vs 6±8, p= 0.004 for CRP, 38±59 vs 12±17, p=0.02 for SAA at the 3 rd visit, 41±17 vs 24±12, p= <0.001 for ESR, 16±18 vs 4±5, p= 0.01 for CRP, 22±30 vs 10±16, p=0.002 for SAA at the 6 th visit). SAA was the only marker that demonstrate the significance between subgroups at the 12 th month (12±10 vs 8±11, p= 0.007). In active GPA subgroup, SAA and vWF at the 3 rd visit and vWF at the 6 th visit were found significantly high compared to inactive patients. Sensitivity and specificity were found as 88-70%, 79-84% for ESR levels of 35 mm/h, 83-65%, 86-84% for CRP levels of 5-8 mg/L 72-50%, 90-80% for SAA levels of 10-11 mg/L at the initial and 6 th months visits in TA cohort. At the 12 th month visit, SAA levels of 9 mg/L, was the only marker reaching the significant sensitivity (50%) and spesificity (83%) for predicting activity. References: In a well established and prospective cohort of TA, SAA has found to be a comparable sensitivity and specificity with ESR and CRP for predicting activity. It's been observed that sensitivity of ESR, CRP had a trend towards to decrease in time which could be related to the decreasing activity during the follow-up. SAA was the only laboratory parameter which maintained its specificity in contrast to conventional biomarkers. Disclosure of Interest: None Declared